Do it (Chinese edition supplement) - Hu Fang; Obrist, Hans Ulrich (Vitamin Creative Space, 2008)
do it (Chinese edition) is the most up-to-date development of the do it project and includes new contributions of do it proposals (in English) by 26 energetic artists from China/within Chinese context. With do it in hand, you will be able to make a work of (someone else's) art yourself. do it has provided "how to" pages of instructions written by more than 200 of the most important artists and writers working today since its initiation by Hans Ulrich Obrist in dialogue with Christian Boltanski and Betrand Lavier in 1993.
English; Chinese
Keywords: Art- Society; Civic engagement; N7560-8266 Visual Arts. Special subjects of art